A Commonwealth Princess? - Jess Carniel (Persona Studies, 2021)
Prior to the Sussexes’ departure from their roles as senior royals, there was a significant attempt to construct for the Duchess of Sussex the persona of the “Commonwealth Princess”. There were two main purposes to this persona. The first was to use both the Duke and Duchess of Sussex and their popularity to leverage a more modern face to monarchy in the Commonwealth. The second purpose, stemming from this, was to maintain and strengthen contemporary relations with Commonwealth nations. Markle’s biracial identity was an important part of this strategy and persona as it became a means to connect to colonised people of colour.